Effects of BN layer on photoelectric properties and stability of flexible Al/Cu/ZnO multilayer thin film. Issue 10 (July 2020) - Li, Bao-jia; Yang, Guang-yu; Huang, Li-jing; Wang, Tian-yu; Ren, Nai-fei
Abstract: This study focused on utilizing a boron nitride (BN) layer to improve the photoelectric property stability of the flexible Al/Cu/ZnO multilayer thin film, which was prepared on a polyethylene terephthalate (PET) substrate by radio frequency (RF) magnetron sputtering. By analyzing surface morphology, chemical composition and photoelectric properties of flexible BN/Al/Cu/ZnO multilayer films with different BN layer thicknesses, the BN/Al/Cu/ZnO film with a 100-nm-thick BN layer (BN100 /Al/Cu/ZnO), which had the best comprehensive photoelectric property with a figure of merit of 0.82 × 10 −3 Ω −1, was chosen to further study the performance stability with storage temperature and time. It was found that as compared to the Al/Cu/ZnO film, the BN100 /Al/Cu/ZnO film had more stable photoelectric properties at different storage temperatures and times, which was inferred to be attributed to the excellent heat and oxidation resistances of the BN layer that were conducive to avoiding surface damage and oxidation of the film. The results in this work demonstrate the key role of the BN layer in enhancing photoelectric property stability of the flexible Al/Cu/ZnO film, and may provide a feasible strategy for improving thermal and long-time stability of single-layer or multilayer flexible transparent conductive films.